Application of Performance-Based Plastic Design (PBPD) method for 3D steel structures. (15th November 2019) - Ghamari, Masoud; Shooshtari, Mohammad
Abstract: The Performance-Based Plastic Design (PBPD) method, introduced last decade, is an energy-based procedure. This method which is proposed for 2D frames has several stages. At the first stage, a pre-selected global yield mechanism and a target drift are selected. Then, the energy equilibrium equation is developed for a frame to calculate the base shear. At the end stage, designing the beams and columns is done for just one-bay of the planar frame. Since in PBPD-2D procedure the components of energy equilibrium equation are based on the planar frames, it does not consider the adjacent frames effect in 3D design problems so it is necessary to do research about developing PBPD method in 3D frames. The main scope of this paper is to apply the 3D effect on PBPD method. In the current research, the nonlinear distribution of base shear in plan has been found by nonlinear time-history analysis and processed by artificial neural networks. To fortify the results and analyses, 3D and nonlinear modeling is chosen. In the current research, the effect of earthquake power in the nonlinear base shear distribution in plan is considered by looking at the earthquake magnitude and the PGA. Since the earthquake energy is the best structural damage index, in this way, one can design 3D structures by PBPD method adjusted to the desired damage level. In this regards, three special moment frames are designed according to PBPD-2D procedure and proposed PBPD-3D procedure. The results of nonlinear time-history analysis show that the PBPD-2D method could not satisfy the weak beam- strong column criterion and the global yield mechanism in 3D designing, whereas the proposed method in this research, PBPD-3D, satisfies the mentioned criterion successfully.